Low Dose Pig Anti-Influenza Virus Monoclonal Antibodies Reduce Lung Pathology but Do Not Prevent Virus Shedding - Paudyal, Basudev; McNee, Adam; Rijal, Pramila; Carr, B. Veronica; Nunez, Alejandro; McCauley, John; Daniels, Rodney S.; Townsend, Alain R.; Hammond, John A.; Tchilian, Elma (Frontiers in Immunology, 2021)
We have established the pig, a large natural host animal for influenza, with many physiological similarities to humans, as a robust model for testing the therapeutic potential of monoclonal antibodies (mAbs). In this study we demonstrated that prophylactic intravenous administration of 15mg/kg of porcine mAb pb18, against the K160-163 site of the haemagglutinin, significantly reduced lung pathology and nasal virus shedding and eliminated virus from the lung of pigs following H1N1pdm09 challenge. When given at 1mg/kg, pb18 significantly reduced lung pathology and lung and BAL virus loads, but not nasal shedding. Similarly, when pb18 was given in combination with pb27, which recognised the K130 site, at 1mg/kg each, lung virus load and pathology were reduced, although without an apparent additive or synergistic effect. No evidence for mAb driven virus evolution was detected. These data indicate that intravenous administration of high doses was required to reduce nasal virus shedding, although this was inconsistent and seldom complete. In contrast the effect on lung pathology and lung virus load is consistent and is also seen at one log lower doses, strongly indicating that a lower dose might be sufficient to reduce severity of disease, but for prevention of transmission other measures would be needed